Agronomic Evaluation of Biofarming Techniques for Forage Production in Coconut Gardens - Sansamma George (Department of Agronomy, College of Agriculture, 1996)
Two field experiments were conducted at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala State to study the potential of biofarming techniques for forage production in coconut gardens. The study was carried out for a period of two years from September 1993 to August 1995. The influence of the different nutrient management techniques on uptake of nutrients, quality of produce and physico-chemical properties of soil was also investigated. In experiment no.1. the influence of two nitrogen fixing organisms., viz. Azospirillum and Azotobacter and the role of Vesicular Arbuscular Mycorrhiza (VAM) in improving the growth and production of guinea grass and congosignal was studied under inoculation alone and also in combination with chemical fertilizers. The nitrogen fixers were tested under varying levels of fertilizer nitrogen and for VAM the level of phosphorus varied between treatments. The prospects for vermicompost use for guinea grass production was examined under experiment no. 2. It was also envisaged to compare the impact of integrated use of manures and fertilizers with the continuous use of chemical fertilizers alone. Results of experiment no.1 revealed that Azospirillum inoculation alone and in combination with fertilizers had significant positive influence on guinea grass production. Azotobacter inoculation showed only limited effects on growth and yield of the forage grass during the first year but the effect was significant during the second year. The results indicated that 25 per cent of the recommended nitrogen could be saved through the use of either of the biofertilizers. VAM inoculation when combined with full dose of recommended fertilizer nitrogen and potassium, showed significant superiority over the POP treatment at 0, 25 and 50 per cent phosphorus doses while the 75 percent P dose gave comparable yields. The quality parameters of the forage recorded values on par or superior to that of the recommended fertilizer treatment. The use of biofertilizers improved the net income and benefit : cost ratio from guinea grass cultivation. The inoculation treatments were found to have a favourable influence on the physical and chemical properties of the soil. Integrated use of the nitrogen fixing organisms with chemical fertilizers was found effective for Congosignal cultivation. Pooled analysis studies indicated that when inoculated with either Azospirillum or Azotobacter, 50 per cent of the recommended fertilizer nitrogen was adequate for yields. VAM inoculation alone elicited significant yield increase over the absolute control. Combind doses of VAM with chemical fertilizers at all levels of applied phosphorus responded more or less similar to the recommended fertilizer treatment. This indicated the possibility of completely substituting the need for fertilizer phosphorus in VAM inoculated congosignal. The VAM effect in promoting growth and yield of the forage was found to decline in the presence of applied phosphorus. The data on economics also favoured the use of biofertilizers. Experiment no. 2 revealed that guinea grass responded well to integrated use of manures and fertilizers. As per pooled analysis vermicompost @ 5 t ha-1 or Farm yard manure @ 10 t ha-1 when combind with 75 per cent of the recommended NPK were comparable with the 100 per cent NPK treatment. Application of the organic manures improved the quality of the produce. The physic-chemical properties of the soil was also favourably influenced by the integrated use of manures and fertilizers. The economic analysis of the data emphasised the need for reducing the reliance on purchased inputs. Coconut yield was found favourably influenced by intercropping of the fodder grasses.